PENYELAMATAN PERUSAHAAN MELALUI RESTRUKTURISASI UTANG (STUDI DI PT GARUDA INDONESIA (PERSERO) TBK) - Kurniawati, Tintin; Kerti, N.G.N. Renti Maharaini (Tribuere, 2023)
PT. Garuda Indonesia (Persero) Tbk is the national flag carrier airline and the only state-owned aviation industry in Indonesia. The Covid-19 pandemic caused PT Garuda Indonesia (Persero) Tbk to be in a technically bankrupt condition and threatened with bankruptcy after the postponement of debt payment obligations on December 9 2021. The main issue that will be raised in this research is whether debt restructuring is the right step in this effort. saving the company and what efforts can be made by the government as the company's shareholder in order to save PT. Garuda Indonesia (Persero) Tbk. This thesis was written using descriptive normative legal research methods, using primary and secondary data, analyzed qualitatively and drawing conclusions based on deductive logic. Based on the results of the research conducted, it can be concluded that based on article 1 point 11 of the Law on State-Owned Enterprises, restructuring is an effort carried out in the context of restructuring State-Owned Enterprises, one form of restructuring is debt restructuring, considering the large number of creditors and complex debt restructuring through Postponement of Debt Payment Obligations is the right step. The results of the debt restructuring helped improve the company's financial condition, with a recovery rate of 19%. However, to improve the condition of the company, other efforts are still needed, namely by restructuring management through rightsizing the number of employees, renegotiating aircraft rental leases, evaluating loss-making flight routes and maximizing the cargo and logistics business. Apart from that, efforts that can be made by the government as a shareholder based on Article 5 of Government Regulation Number 44 of 2005 can be carried out through additional State Capital Participation.